PENDEKATAN KOMUNIKATIF (AL-MADHAL AL-ITTISHAL) DALAM PEMBELAJARAN BAHASA ARAB - Kartini Kartini (AL TAJDID, 2010)
Communicative approach (al-madhal al-ittishali) in study of Arabic language that create to competition as  purpose study  that direct to procedure of language skill, that consist of attention (istima’), speaking (kalam), reading (qiraah), and writing (kitabah). Communication approach (al-madhal           al-ittishal) to stimulate students to learning activity. The used of communication approach activity, that is functional of communication language that another to share information and information process and social interaction activity that is dialog, simulation, debating, and another discussion activity.